High Diagnostic Yield of Targeted Next-Generation Sequencing in a Cohort of Patients With Congenital Hypothyroidism Due to Dyshormonogenesis - Stoupa, Athanasia; Al Hage Chehade, Ghada; Chaabane, Rim; Kariyawasam, Dulanjalee; Szinnai, Gabor; Hanein, Sylvain; Bole-Feysot, Christine; Fourrage, Cécile; Nitschke, Patrick; Thalassinos, Caroline; Pinto, Graziella; Mnif, Mouna; et al. (Frontiers in Endocrinology, 2021)
Objective: To elucidate the molecular cause in a well-characterized cohort of patients with Congenital Hypothyroidism (CH) and Dyshormonogenesis (DH) by using targeted next-generation sequencing (NGS). Study design: We studied 19 well-characterized patients diagnosed with CH and DH by targeted NGS including genes involved in thyroid hormone production. The pathogenicity of novel mutations was assessed based on in silico prediction tool results, functional studies when possible, variant location in important protein domains, and a review of the recent literature. Results: TNGS with variant prioritization and detailed assessment identified likely disease-causing mutations in 10 patients (53 %). Monogenic defects most often involved TG, followed by DUOXA2, DUOX2 and NIS and were usually homozygous or compound heterozygous. Our review shows the importance of the detailed phenotypic description of patients and accurate analysis of variants to provide a molecular diagnosis. Conclusions: In a clinically well-characterized cohort, TNGS had a diagnostic yield of 53%, in accordance with previous studies using a similar strategy. TG mutations were the most common genetic defect. TNGS identified gene mutations causing DH, thereby providing a rapid and cost-effective genetic diagnosis in patients with CH due to DH.